2021
DOI: 10.1038/s41598-021-02371-3
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic brain injury in the presence of Aβ pathology affects neuronal survival, glial activation and autophagy

Abstract: Traumatic brain injury (TBI) presents a widespread health problem in the elderly population. In addition to the acute injury, epidemiological studies have observed an increased probability and earlier onset of dementias in the elderly following TBI. However, the underlying mechanisms of the connection between TBI and Alzheimer’s disease in the aged brain and potential exacerbating factors is still evolving. The aim of this study was to investigate cellular injury-induced processes in the presence of amyloid β … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 116 publications
0
2
0
Order By: Relevance
“…Advanced optical imaging techniques, such as widefield calcium imaging in animals, has provided a unique opportunity to study brain function by enabling recording of the neural activity with high temporal and spatial resolutions. Indeed, such a technique has been recently used to study the relationship between the brain function and behavior [15][16][17][18][19], as well as the relationship between the brain function and injury [20][21][22][23][24][25][26]. Brain FC networks have also been investigated using calcium signals [16,22,[27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Advanced optical imaging techniques, such as widefield calcium imaging in animals, has provided a unique opportunity to study brain function by enabling recording of the neural activity with high temporal and spatial resolutions. Indeed, such a technique has been recently used to study the relationship between the brain function and behavior [15][16][17][18][19], as well as the relationship between the brain function and injury [20][21][22][23][24][25][26]. Brain FC networks have also been investigated using calcium signals [16,22,[27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggested that tau phosphorylation induced by severe closed TBI is linked to the cellular prion protein [43]. Several studies found both Aβ and tau accumulation after TBI [44][45][46][47][48][49][50][51], affecting neuronal survival, glial activation, neuroinflammation, and other pathomechanisms, thus indicating overlapping pathways between TBI and AD [1,52], while others suggested vascular disorders as promoting factors [53].…”
Section: Introductionmentioning
confidence: 99%